Website Content Analysis Using Clickstream Data and Apriori Algorithm - Supriyadi Supriyadi; Yani Nurhadryani; Arif Imam Suroso (Universitas Ahmad Dahlan, 2018)
Clickstream analysis is the process of collecting, analyzing, and reporting data of visited pages by visitor at the time of mouse clicks. Clickstream data are generally stored on a web server in the access.log file including IP Address data, reference pages, and access time. This study aims to analyze clickstream data by converting into the form of a comma sparated value (csv) so that the string inside of it could be grouped and stored in a database. The important information in the database was processed and retrieved by using one of the techniques in web mining called apriori algorithm analysis. Apriori algorithm implementation was done at the time of reading the database and table query analysis on the software developed. Results of this study were the statistics describing the level of access to web pages that were very helpful for web developers to develop web sites.